PROBLEMS OF RESTORATION OF MENSTRUATION AND REPRODUCTIVE FUNCTION AFTER CHILDBIRTH (Academia Science Repository, 2023)
The problem of restoration of menstrual and childbearing function after childbirth has not been adequately reflected in the literature, the restoration of reproductive function against the background of lactational amenorrhea is the cause of a short intergenetic interval, abortions in lactating women, the frequency and duration of lactational amenorrhea after physiological and complicated childbirth, including surgical due to with the widespread introduction of the principles of a benevolent attitude towards the child and breastfeeding into the obstetric institutions of the republic, this problem becomes relevant.